1975
DOI: 10.1055/s-0028-1093719
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of the Pancreas and the Intestine to the Regulation of Lipolysis in Birds - I. Existence of Highly Potent Lipolytic Factors in Ileum Extracts

Abstract: Duck intestinal extracts were separated into three main peaks of proteins by chromatography on P6 BioGel columns. The first, which crossreacted with glucagon antibodies, gut "GLI", did not stimulate lipolysis in isolated chicken adipocytes. Both second and third peaks, corresponding to smaller molecular-size peptides were even more lipolytic than pancreatic glucagon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Inhibition is not, however, provided by insulin, which has high antilipolytic activity in mammals (McCumbee and Hazelwood 1978). A third pancreatic hormone, avian pancreatic polypeptide is antilipolytic in birds (McCumbee and Hazelwood 1978), as is a glucagonlike material found in the intestine (Krug and Mialhe 1975;Krug 1978). The physiological role of these substances in cold stress or exercise has not been investigated.…”
Section: Mobilization and Oxidation Of Energy Substrates In The Coldmentioning
confidence: 95%
See 1 more Smart Citation
“…Inhibition is not, however, provided by insulin, which has high antilipolytic activity in mammals (McCumbee and Hazelwood 1978). A third pancreatic hormone, avian pancreatic polypeptide is antilipolytic in birds (McCumbee and Hazelwood 1978), as is a glucagonlike material found in the intestine (Krug and Mialhe 1975;Krug 1978). The physiological role of these substances in cold stress or exercise has not been investigated.…”
Section: Mobilization and Oxidation Of Energy Substrates In The Coldmentioning
confidence: 95%
“…Harvey et al (1985) found increases in glucagon levels in exercising mallard ducks, suggesting a physiological role of glucagon under conditions of accelerated energy demand. Other hormones, or putative hormones that have lipolytic activity in birds and could potentially contribute to physiological regulation of lipolysis, include growth hormone (LeClerq 1984) and two intestinal peptides (Krug and Mialhe 1975;Krug 1978). Lipid mobilization can also potentially be modulated by altering levels of inhibitory hormones.…”
Section: Mobilization and Oxidation Of Energy Substrates In The Coldmentioning
confidence: 98%
“…In addition, glucagon is a very strong lipolytic factor [3,21,22]. Fifteen minutes after a single IV injection of 2 ~tg glucagon/kg, plasma FFA are doubled, while adipose tissue of fed or fasted ducks responds in vitro to very low concentrations of the hormone [8], as low as 50 pg/ml. We have therefore tried to explain why total pancreatectomy is followed by such a delayed drop in plasma FFA [3].…”
Section: The Effect Of Pancreatectomy On Plasma Ffamentioning
confidence: 99%
“…1. Compensation for pancreatic glucagon by other lipolytic agents, the anterior pituitary and the intestine being possible sources [3,6,7,8] (APP being secreted in the fed animal [9], and somatostatin having been shown to have an indirect effect in mammals [10]).…”
mentioning
confidence: 99%